The First WHO International Standard for Adalimumab: Dual Role in Bioactivity and Therapeutic Drug Monitoring - Wadhwa, Meenu; Bird, Chris; Atkinson, Eleanor; Cludts, Isabelle; Rigsby, Peter (Frontiers in Immunology, 2021)
Adalimumab products continue to widen patient access and reduce costs with substantial benefit to healthcare systems. However, their sustainability and long-term success is highly dependent on maintaining quality, safety and efficacy while minimizing any risk of divergence during evolution. In recognition of this need, the World Health Organization in 2019 established the 1st International Standard (IS) for Adalimumab with defined units for individual bioactivities. Two candidate standards were manufactured as per WHO recommendations. Analysis of extensive datasets generated by testing common samples by multiple stakeholders using their own qualified assays in a large international study showed comparable biological activity for the candidates for the different functions. Use of a common adalimumab standard decreased bioassay variability and improved agreement in potency estimates. Study data supports the utility of the adalimumab IS as an important tool for assuring analytical assay performance, bioassay calibration and validation, identifying and/or controlling changes in bioactivity during life-cycle management and global harmonization of adalimumab products. A separate multi-centre study with involvement of hospital and clinical diagnostic laboratories examined the suitability of the adalimumab IS for therapeutic drug monitoring assays by testing a panel of adalimumab spiked serum samples along with the IS and in-house standards in diverse immunoassays/platforms routinely used for assessing trough levels. Excellent agreement in estimates for sample adalimumab content was observed regardless of the standard or method used, with inter-laboratory variability also similar regardless of the standard. This data, for the first time, provides support for the extended applicability of the adalimumab IS, based on its mass content, in therapeutic drug monitoring assays. The adalimumab IS, in fulfilling clinical demand, can help towards standardizing and harmonizing clinical monitoring assays for informed decision-making or personalized treatment strategies for better patient outcomes. Collectively, a significant role for the adalimumab IS in assuring the quality, safety and efficacy of adalimumab products globally is envisaged.